A Comparative Study of the Teaching English Writing in Senior High Schools in Indonesia and Japan - Sonny Elfiyanto; Seiji Fukazawa (VELES Voices of English Language Education Society, 2022)
The aim of this study is to investigate Indonesian and Japanese English teachers’ perspectives about English writing, to examine current techniques in the teaching of writing used by senior high school teachers in Indonesia and Japan, and how to know whether there are some differences and/or similarities between teaching methodologies of English writing in both countries. This study surveyed 44 Indonesian senior high school teachers and 43 Japanese senior high school teachers through a questionnaire and an interview. The findings indicated that the Indonesian and Japanese senior high school teachers have different teaching methodologies for the improvement of students’ abilities in English writing. Lastly, a conclusion is provided, accompanied by limitations of the study and suggestions for further study.